(Ni, Co)Se@Ni(OH)2 heterojunction nanosheets as an efficient electrocatalyst for the hydrogen evolution reaction. Issue 1 (15th December 2020) - Du, Yunmei; Zhao, Huimin; Wang, Wensi; Yang, Yu; Wang, Minghui; Li, Shaoxiang; Liu, Yanru; Wang, Lei
Abstract : A heterogeneous structure composed of a selenide and Ni(OH)2 can accelerate electron transfer and enrich active sites. Abstract : A heterogeneous structure formed by coupling two or more phases can reinforce the activity of active sites and expedite electron transfer, which is conducive to boosting its electrocatalytic activity. Herein, we designed nickel foam supported (NiCo2 )Se@Ni(OH)2 (NCS@NH) heterojunction nanosheets by a two-step method. First of all, the NiCo2 S4 @Ni(OH)2 (NiCo2 S4 @NH) nanosheets coated on nickel foam were acquired via a hydrothermal method. In the selenization treatment that followed, NiCo2 S4 @NH was converted into NCS@NH heterogeneous nanosheets in which the selenide nanoparticles decorated on the surface of the Ni(OH)2 nanosheets formed heterojunction interfaces, and the heterogeneous structure could accelerate electron transfer, thus improving the catalytic activity. The Ni(OH)2 nanosheets can adequately contact the electrolyte and promote the decomposition of water. Meanwhile, the thickness of the Ni(OH)2 nanosheets gradually decreases with the increase of Co doping (1.5–2.5 mmol), consequently affecting the HER properties. Notably, when the amount of Co salt added is 2 mmol, NCS@NH exhibited superior HER properties (with a voltage of 253 mV at 100 mA cm −2 ) and excellent stability for 24 h.